Respon akut tekanan darah akibat konsumsi kopi pada wanita sehat - Yusni, Yusni; Yusuf, Hanifah (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Coffee contains caffeine. Caffeine is the main component that influences the response of the cardiovascular system and blood pressure (BP). Acute response of coffee to increased BP is related to caffeine.Objectives: This study aims to analyze the acute response of coffee consumption on BP in healthy females therefore coffee is an alternative therapy for hypotension.Methods: The research design was a clinical trial. Treatment: black coffee, Gayo’s Arabica, 10 mg, coffee brewed with 150 ml of boiling water, without sugar. BP was examined using a mercury sphygmomanometer and stethoscope. BP each subject was examined twice and averaged. BP was checked 3 times: before, 30, and 60 minutes after coffee consumption. All subjects were non-coffee drinkers. A total of 20 healthy female, 18-20 years old were divided into two groups: the non-intervention (n=9) and intervention (n=11). Data was analyzed by independent and paired sample t-test.Results: Coffee increased systolic 10-20 mmHg (14.09%) and diastolic 3.64 mmHg. Coffee lowers 36.36% of subjects with hypotension. There was no difference between systolic pre-test (101.11±12.69 vs 100.00±10.00 mmHg; p=0.83) and 30 minutes post-intervention (102.22±13.01 vs 101.82±9.82 mmHg; p=0.94). There were a significant differences in systolic after 60 minutes post-intervention (103.33±11.18 vs 114.09±5.84 mmHg; p=0.01*) between non-intervention and intervention. There was no difference between diastolic pretest (70.00±5.59 vs. 68.18±6.03 mmHg; p=0.49), 30 minutes (70.59±5.27 vs. 70.00±6.33 mmHg; p=0.83), and 60 minutes post-intervention (70.00±5.59 vs. 71.82±4.04 mmHg; p=0.41) between non-intervention and intervention. Data showed that systolic was significantly different (p=0.00*) after 60 minutes of coffee consumption in the intervention group. Conclusion: The acute response of coffee consumption to systolic increases was after 60 minutes and not 30 minutes of coffee consumption. Coffee doesn’t affect diastolic in healthy women, but it needs further research.